Pilne!
Z góry dzieki za szybką odp ;)
Dam naj ;)

1.
xy² * 2x =
3ty * ⅓t =
4a² * 2ab =
3xt * (-t) =
3xt * (-t) *2x² =
4yb² * ½y =
4yb² * ½y * (-5b) =

2.Uzupełnij:
12x²y³= 12xy * ..........
12x²y³= 6x² * ..........
12x²y³= 4y * ..........

6a³b= ½ab * ..........
6a³b= 3a² * ..........
6a³b=2a²b * ..........

8a²b³c= 2abc * .........
8a²b³c= 4ac * ..........
8a²b³c= ½bc * ..........

2

Odpowiedzi

2010-01-25T20:18:51+01:00
1.
xy² * 2x = 2x²y²
3ty * ⅓t =
4a² * 2ab = 8a³b
3xt * (-t) = -3xt²
3xt * (-t) *2x² = -3xt² *2x² = -6x³t²
4yb² * ½y =
4yb² * ½y * (-5b) =

2.Uzupełnij:
12x²y³= 12xy * xy²
12x²y³= 6x² * 2y³
12x²y³= 4y * 3x²y²

6a³b= ½ab * ..........
6a³b= 3a² * 2ab
6a³b=2a²b * 3a

8a²b³c= 2abc * 4ab²
8a²b³c= 4ac * 2ab²
8a²b³c= ½bc * ...
12 3 12
Najlepsza Odpowiedź!
2010-01-25T20:23:10+01:00
1)
Xy2*2x= 2x2y2
3ty*1/3t = t2y
4a2*2ab=8a3b
3xt*(-t)= -3xt2
3xt*(t)*2x2=-3xt2*2x2=-6x3t2
4yb2*1/2y*(-5b)=2y2b2*(-5b)=10y2b3


2)
12xy*xy^2
6x^2*2xy^2
4y*3x^2y^2

6a³b= ½ab * 12a^2
6a³b= 3a² * 4ab
6a³b=2a²b * 3a

8a²b³c= 2abc *4ab^2
8a²b³c= 4ac * 2ab
8a²b³c= ½bc *16a^2b^2
^ znaczy podniesione do potęgi:P
16 3 16